Assessing the Allochthonous and Autochthonous sediment inputs in conjunction with catchment and in situ depositional conditions in several shallow lakes of the Danube Delta and the Black Sea littoral area (Geo-Eco-Marina, 2020)
In order to assess the origin and contribution of the autochthonous and allochthonous material to the recent natural sedimentation, analyses of the main lithological components, i.e., total organic matter (TOM%), total carbonates (CAR%) and minerogenic fraction (SIL%), were performed on several bottom sediment samples, gathered from five lakes. These lakes represent different environmental situations (i.e., deltaic, lagoon and littoral/coastal environment), but they are all influenced by the river/rivulet input of water and sediments. Sampling techniques take into consideration an undisturbed substratum (0 – 30 cm) from surface and subsurface bottom sediment samples, that were collected, using Van Veen Grab Sampler, from 141 stations, along the selected longitudinal and latitudinal transects of the lakes. Loss On Drying and, respectively, Loss On Ignition Methods were used to estimate the percentage contents of TOM%, CAR% and SIL%. The main physical processes that influence the sediment deposition within these lakes are generally related to hydrodynamics and sediment transport, climatic conditions, and environmental variables within the depositional areas. The results reveal a similar alternating lithology between organic-rich sediments (low energy environmental conditions), mineral-rich sediments (higher energy environmental conditions) and ”transitional”/mixed sediments (mixed sediment environments). In complex environments, like the study area, with both fluvial input and high in situ productivity, separating and quantifying the two constituents is not straight forward. Further investigations are required to corroborate the findings of this paper for recent sediment accumulations in environments with mixed sedimentary processes.
Keywords: bottom sediment; physical-chemical characteristics; spatial variability; organic matter content; transitional environment